PENGEMBANGAN APLIKASI KAMUS BAHASA INDONESIA – SENTANI BERBASIS WEB - Dwi Saputro, Agung; Kuddi, Bobi Frans (Jurnal Ilmiah Sistem Informasi, 2024)
In previous research conducted by (Saputro & Seru, 2023) titled "Design of an Indonesian-Sentani Dictionary Application Based on Android," it was shown that the application is functioning according to the design that was made. However, the application still has a fundamental drawback, which is that it can only be accessed using Android smartphones. This deficiency is considered necessary to be developed and improved to produce a more perfect language application. The purpose of this research is to develop the previous application, which is still Android-based, into a web-based application. The method used in this research is the Research & Development (R&D) method. The R&D method was chosen because the application being developed is an enhancement of an existing application. The stages of this method are data collection, coding design, and testing. The results of this research show that the developed website is functioning according to the designed layout, the website is capable of displaying Indonesian-Sentani words and vice versa, and the website also has a sound feature that can convert text to speech.